How to solve 3t - 7 = 5t, then 6t=

Answers

Answer 1
Answer: 3t-7=5t
5t-3t=-7
2t=-7
t=-7/2

6t= 6(-7/2)
6t=3*(-7)
6t=-21
Answer 2
Answer:

Answer:

21

Step-by-step explanation:

5T-3T= -7

THEN, 2T =-7

THEN, DIVIDE

T= 7/2

THEN,

6T= 6(-7/2)

6T= 3(-7)

6T= (21)


Related Questions

Which amounts of materials satisfy the relationship?2 cubic yards of compost, 8 cubic yards of topsoil4 cubic yards of compost, 5 cubic yards of topsoil1 cubic yard of compost, 12 cubic yards of topsoil3 cubic yards of compost, 12 cubic yards of topsoil
Mindy can type 40 words per minute. How many words can she type in 5 minutes?​
The total number of laps needed to complete a bike marathon is 75. Kayla completed at least 68 laps. How many possible complete laps could Kayla have completed. Please show work. I'm offering lots of points for this question. Thanks you guys.
The sum of digits of a 3 digit number is 12. Three times the hundreds digit minus twice the tens digit is 5. If six time the units digit is added to four times the tens digit, the result is 50. Find the number.
Your new job guarantees you an eight percent raise for each year with the company. If your initial salary is $42,200, write an equation to model your salary after t years

IT'S TIMED NEED HELP ASAP!! Find the measure of angle C

Answers

Answer: 250 degrees

Step-by-step explanation:

Answer:

x=(1)/(7)

15(1/7)+5= 7.14 (rounded o the nearest hundredths)

I hope this is good enough:

HEEEEEELP

question in the attached picture

Answers

1) x^(2) +2x-10=0
a=1
b=2
c=-10
x= \frac{-(2) +or-  \sqrt{ 2^(2)+4(1)(-10) } }{2(1)}
x= (-2 + or - √(4+40) )/(2)
x= (-2 +or- √(44) )/(2)
x= (-2+or- 2√(11) )/(2)
x= -1+or- √(11)
√(11)=3.32
-1+3.32 = 2.32
-1-3.32 = -4.32

2) 
x^(2) -2x-9=0
a=1
b=-2
c=-9
x= \frac{-(-2)+or- \sqrt{ (-2)^(2)+4(1)(-9) } }{2(1)}
x= (2+or- √(4+36) )/(2)
x= (2+or- √(40) )/(2)
x= (2+or-2 √(10) )/(2)
x=1+or- √(10)
√(10) =3.16
1+3.16 = 4.16
1-3.16 = -2.16

3) 
x^(2) -9x+5=0
a=1
b=-9
c=5
x= \frac{-(-9)+or- \sqrt{(-9)^(2)-4(1)(5) } }{2}
x= (9+or- √(81-20) )/(2)
x= (9+or- √(61) )/(2)
x= (9)/(2) +or-  ( √(61) )/(2)
√(61) = 7.81
(7.81)/(2) =3.91
(9)/(2)=4.5
4.5+3.91 = 8.41
4.5-3.91 = 0.59

A tangent-tangent angle intercepts two arcs that measure 135 degrees and 225 degrees. What is the measure of the tangent tangent angle?

Answers

Answer:

M=45 degrees

Step-by-step explanation:

It is given that A tangent-tangent angle intercepts two arcs that measure 135 degrees and 225 degrees, thus in this the vertex lies outside, therefore

The measure of the tangent tangent angle is the half of the difference of the two given arc, that is

M=(1)/(2)(225-135)

M=(90)/(2)

M=45 degrees

Therefore, The measure of the tangent tangent angle is 45 degrees.

225-130/2=45degree..

The first term of an arithmetic sequence is -5, and the tenth term is 13. Find the common difference.a. 8/9
b. 2

Answers

Hello,

Answer B
a_(0)=-5\na_(9)=a_(0)+9*r\n13=-5+9*r\nr= (18)/(9)=2

Ahmed spent 2/3 of his money on a burrito and a water. The burrito coast 2 times as much as the water. The burrito cost $4, how much money does Ahmed have left?

Answers

The burrito costs twice as much as water. Let's assume the water costs $w
$4=2w
w=$2 
Ahmed spent $2+$4=$6
2/3 of the total amount = $6
Total amount =$6x3/2
                      =$9
if a burritto is twice as much as water the the water is two dollars. if Ahmed spent 2/3 of his money then( 4+2=6) for burrito and water it means he had nine dollars originally so he is left with 3 dollars.  

I'm having a hard time with this one solve for y 3y+7=28?

Answers

3y+7=28     Change 7 to right
3y = 28 - 7   Do subtraction
3y = 21        Divide both sides by 3
y = 7             Get result
3y+7=28\n 3y=21\n y=7